PEMBUATAN PROGRAM APLIKASI INVENTORI PADA PD KAPUAS - Kiki Kiki; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
The aim of this thesis is to assist the process of listing and checking items as well as facilitating the transaction process in PD. KAPUAS storehouse. The Method used in developing this application program is SDLC (System Development Life Cycle). This application is desktop based that holds informations regarding PD. KAPUAS inventory system. The use of this application is to supervise the product acquisition in PD. KAPUAS storehouse. In addition to supervising the items, this application could generate reports with computerized one. Those reports are; received items, report of the exit items, also report of return items from suppliers. This application was designed with Visual Studio 2012, using SQL Server Management Studio 2012 as the database system, Crystal Reports is also used to generate the reports.The testing phase results gave conclusion that the system created is able to be used, and could help PD. KAPUAS to monitoring their inventory.